B 0 Magnetic Field Conditions in the Human Heart at 3 T Across One Thousand Subjects: A Numerical Simulation Study - Shang, Yun; Theilenberg, Sebastian; Peng, Boyu; Schreiber, Laura M.; Einstein, Andrew J.; Jambawalikar, Sachin R.; Juchem, Christoph (NMR in biomedicine, 2025)
Functional scans in cardiovascular magnetic resonance (CMR) adopting bSSFP sequences suffer from dark band artifacts due to B 0 inhomogeneity. The best remedy to mitigate this issue is through cardiac B 0 shimming. The development of an optimal B 0 shim strategy for the human heart is hindered by a limited understanding of B 0 conditions in clinical diagnostic orientations of CMR. Here, we present high‐resolution B 0 distributions in cardiac imaging planes, derived from simulations utilizing high‐resolution computed tomography (CT) images from 1008 subjects, and present an oblique slicing method to derive such B 0 distributions. This study also presents a theoretical analysis of spherical harmonic B 0 shimming at 3 T using a static global approach and slice‐specific dynamic shim updating in the short‐axis view of human hearts. The characteristics of cardiac B 0 conditions along with spherical harmonic shimming were correlated with the subjects' demographic parameters, with weak or no correlations, suggesting limited demographic commonality and predominantly subject‐specific characteristics in cardiac B 0 . The segmented lung volume shows more significant associations and relatively higher correlations with B 0 conditions, indicating that B 0 conditions in the heart rely on the anatomy surrounding the heart more than overall body shape and size. This research provides a basis for the development of optimized cardiac B 0 shim strategies.